Integration of Pancasila Values in Economic Legal engineering for National Development - Yahya, Alvin; Auliaurahman; Fadlulloh, Qolbi Hanif; Nurdin, Nazar; Imanullah, Moch Najib (Universitas Islam Negeri Walisongo Semarang, 2024)
This article explores the philosophical and constitutional foundations that form the basis for the development of economic law in Indonesia. As is known, Indonesian legal problems such as economic inequality, corruption, legal uncertainty, and complicated bureaucracy make it difficult for the Indonesian economy to develop. Laws that should have been engineered for development capital did not go according to plan. This article uses normative legal methods on legislative systematics. The approach in the paper uses a combination of legislative, philosophical and constitutional approaches. The research results show that the philosophical foundations of economic law in Indonesia are based on Pancasila, which functions to create stability, support development, uphold justice, and increase legal literacy. Economic law plays an important role in national development with the principles of faith, benefits, Pancasila democracy and social justice. The Indonesian Constitution emphasizes the principles of kinship and social justice in economic policy, although it is still challenged by capitalistic and socialistic tendencies. This is why it is important to integrate Pancasila values ​​to achieve sustainable and just development in Indonesia. Artikel ini mengeksplorasi dasar-dasar filosofis dan konstitusional yang menjadi dasar pengembangan hukum ekonomi di Indonesia. Seperti diketahui persoalan hukum Indonesia seperti ketimpangan ekonomi, korupsi, ketidakpastian hukum, hingga birokrasi berbelit membuat ekonomi Indonesia sulit berkembang. Hukum yang semestinya direkayasa untuk modal pembangunan tidak berjalan sesuai rencana. Adapun penelitian ini menggunakan metode hukum normatif pada sistematika perundang-undangan. Pendekatan dalam artikel menggunakan gabungan pendekatan perundang-undangan, filsafat dan konstitusional. Hasil penelitian menunjukkan bahwa dasar-dasar filosofis hukum ekonomi di Indonesia yang berlandaskan Pancasila, yang berfungsi untuk menciptakan stabilitas, mendukung pembangunan, menegakkan keadilan, dan meningkatkan literasi hukum. Hukum ekonomi berperan penting dalam pembangunan nasional dengan prinsip-prinsip keimanan, manfaat, demokrasi Pancasila, dan keadilan sosial. Konstitusi Indonesia menekankan prinsip kekeluargaan dan keadilan sosial dalam kebijakan ekonomi, meskipun masih tantangan dari kecenderungan paham kapitalistik dan sosialistik. Dari sini penting adanya integrasi nilai-nilai Pancasila untuk mencapai pembangunan berkelanjutan dan berkeadilan di Indonesia